2017
DOI: 10.1016/j.ajodo.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

ENPP1 and ESR1 genotypes associated with subclassifications of craniofacial asymmetry and severity of temporomandibular disorders

Abstract: Introduction We investigated if ACTN3, ENPP1, ESR1, PITX1 and PITX2 genes which contribute to sagittal and vertical malocclusion also contribute to facial asymmetries and TMD before and after orthodontic and orthognathic surgery treatment. Methods One hundred seventy four dentofacial deformity patients were diagnosed as symmetric or subdivided into four asymmetric groups according to PA cephalometric measurements. TMD exam diagnosis and Jaw Pain and Function-(JPF) questionnaires assessed presence and severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 46 publications
(60 reference statements)
0
46
0
Order By: Relevance
“…13 If polymorphisms for mechanosensitive genes augment or diminish signal transduction, thereby modifying responsiveness of the TMJ secondary cartilages to mechanical stimuli, that is unknown. Also unknown is whether asymmetric differences in mechanosensitive genes, like those seen in asymmetric craniofacial anomalies, 22,23 affect unilateral differences in mechanosensitive genes in response to symmetric mechanobehavior.…”
Section: Discussionmentioning
confidence: 99%
“…13 If polymorphisms for mechanosensitive genes augment or diminish signal transduction, thereby modifying responsiveness of the TMJ secondary cartilages to mechanical stimuli, that is unknown. Also unknown is whether asymmetric differences in mechanosensitive genes, like those seen in asymmetric craniofacial anomalies, 22,23 affect unilateral differences in mechanosensitive genes in response to symmetric mechanobehavior.…”
Section: Discussionmentioning
confidence: 99%
“…Genes involved in structural functions, such as ACTN3 (alpha‐actinin‐3), GSTM1 (glutathione S ‐transferase mu 1), MTHFD (C‐1‐tetrahydrofolate synthase, cytoplasmic) and MTRR (methionine synthase reductase), may influence the risk of temporomandibular dysfunction . We can speculate that these genes possibly respond differently to oxidative stress, which leads to the production of nitrous oxide and peroxynitrite, reacts to excessive mechanical overload, and is harmful to DNA, which could promote greater susceptibility to TMD.…”
Section: Discussionmentioning
confidence: 99%
“…When craniofacial asymmetry was present, these patients reported a significantly elevated level of pain and jaw dysfunction. [ 14 ] This coincided with significantly elevated clinical diagnosis of disc displacement with reduction, myalgia, arthralgia and TMD related headache. In discriminating between different patterns of asymmetry, we developed a new posterior anterior cephalometric analysis which distinguishes four anatomic subclassifications (group one—four), each with a different rate of TMD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…This unusual subclassification of asymmetry is very common and results in the highest rate of patient reported TMD symptoms. [ 14 ] Genetic analysis revealed that an additional variant in ENPP1 (rs858339) associated with this asymmetry pattern. Group two and three had the highest rates of reported TMD symptoms, and four had the lowest—even though skeletal imbalance was the most pronounced in this group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation